(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The family’s continuous follow-up of their children at school and their attempt to comprehensively cover their behaviors and activities, the extent of their commitment to performing duties on time, and the extent of their comprehension of the educational material are among the most important components of the success of the educational process, especially for the elementary stage. In order to invest in this relationship and benefit from it in the best possible way, those in charge of the educational institution had to find the appropriate solution that would save time and effort for both the school and the family. In order to organize this process, it was necessary to create a comprehensive software system that would allow the school to manage the educational process and the family to follow up daily through notifications, messages, and other methods. The study aims to identify the possibility of benefiting from mobile applications in managing the details of the educational process in a group of schools in the city of Samawah, as the descriptive survey method was used. The study sample consisted of 80 members (50) teachers and (30) families, randomly selected from schools in the city of Samawah, and to achieve the objectives of the study, a questionnaire was developed that included (30) paragraphs distributed over three fields, the field of smart phone applications for managing the educational process, the field of smart phone applications for managing teachers’ affairs and the field of Smart phone applications to manage the educational process between school and family. The study showed that the acceptability of smartphone applications in the educational process varied according to gender, scientific specialization, and the type of school, whether private or public. The study recommended: Activating smart phone applications and employing them in managing the educational process in city schools and sensitizing teachers, students and their families on the importance of these applications in reducing time and effort.